Diseño óptimo en la producción de una loción perfume (2017)
The main objective of this project is the optimal design of a perfume based on the physicochemical models that controls the transport phenomena and phase equilibrium, associated to a market model that quantifies the consumers' preferences. Is it wanted to apply a nonlinear programing (NLP) based on the product design methodology, capable of relating the consumers' preference (impact, tenacity, diffusion, volume) with macro and microscopic perfume properties and its components concentration. Finally, it is being analyzed physic and economic parameters given an objective function that maximize the product gain. The programming it is been developed in the optimization software Gams'. The obtained results are feasible due to the gain maximization to approximately 1 million of USD per 5 million kg of perfume per year, that take the perfume inside the 20% of the feminine perfume market in Colombia.--Tomado del Formato de Documento de Grado.